PENGUJIAN JANUARY EFFECT : STUDI KOMPARASI PADA BURSA EFEK INDONESIA DAN BURSA SAHAM SHANGHAI PERIODE 2011-2013 - Latanza Hanum Kartikasari (Journal of Business & Banking, 2016)
The January Effect occurred as a result companies that have a strategy to improve it is financial statements. The company will sell stocks that have low values at the end of the year and sell shares favorable to attract investment back at the beginning of next year. January Effect the anomaly that serves low stock Return occurred in December and the highest Return ing January. The purpose of this research was to examine whether there is a phenomenon January Effect on Effect Indonesia Stock Exchange and Shanghai Stock Exchange in Period 2011-2013The variables used in this study are the Return, Abnormal Return and trading volume activity. This research was conducted at the company that is static between years 2011-2013 were in a group LQ45 and SSE50 samples that meet the criteria. The model used is the determination of the sample with purposive sampling method. The tools used are Test One-Way ANOVA and Paired Sample (t-test). The results of analysis showed that look Abnormal Return  stock and Return  there is a difference between January to January in addition to the Indonesia Stock Exchange and Shanghai Stock Exchange by using One-Way ANOVA, while the Paired Sample (t-test) on the Shanghai Stock Exchange there the difference between January to be for January. And for testing of trading volume activity, The January Effect does not occurred in the Indonesia Stock Exchange and Shanghai Stock Exchange.